PENGARUH POLA ASUH ORANGTUA TERHADAP MORAL ANAK USIA 4-5 TAHUN DI RA.TARUNA MULIA KABUPATEN PROBOLINGGO - Eka Agustina Busriyah; Windasari, Indriana Warih (Al-ATHFAL: Jurnal Pendidikan Anak, 2024)
This research aims to determine the influence of parenting styles on the morale of children aged 4-5 years in RA. Taruna Mulia, Probolinggo district. This research uses qualitative methods with a descriptive approach. Sources of data obtained through interviews, observation and documentation. The research was conducted at RA.Taruna Mulia, Gunung Tugel village, Probolinggo district in group A, totaling 17 children with a sample of 6 people. The sample was determined using purposive sampling to make this research more focused and easier. There are several types of parenting styles according to experts, especially Dictator, Lenient, and Popularity. Of these three types, scientists need to be aware of which parenting style is more dominant in the application of young people's ethics. After testing the direction, the analysts observed that there were only two types of parenting styles applied by the guardians, namely the Tyrant and Majority rule parenting styles. which is considered to have a great influence on children's morals. With this research, parents realize that proper parenting will form good morals. Keywords: Parenting patterns; morals; children aged 4-5 years